2000
DOI: 10.1128/iai.68.12.7126-7131.2000
|View full text |Cite
|
Sign up to set email alerts
|

mig-14Is a Horizontally Acquired, Host-Induced Gene Required forSalmonella entericaLethal Infection in the Murine Model of Typhoid Fever

Abstract: We have characterized a host-induced virulence gene, mig-14, that is required for fatal infection in the mouse model of enteric fever. mig-14 is present in all Salmonella enterica subspecies I serovars and maps to a region of the chromosome that appears to have been acquired by horizontal transmission. A mig-14 mutant replicated in host tissues early after infection but was later cleared from the spleens and livers of infected animals. Bacterial clearance by the host occurred concomitantly with an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…For instance, it was confirmed by mutational analysis that the DFI-isolated Salmonella enterica serovar Typhimurium mig14 gene (279) is required for lethal infection of mice (277). Recently, it was shown that mig14 encodes an inner membrane-associated protein that promotes persistent infection, survival within macrophages, and resistance to an antimicrobial peptide (23).…”
Section: Fun Genesmentioning
confidence: 84%
“…For instance, it was confirmed by mutational analysis that the DFI-isolated Salmonella enterica serovar Typhimurium mig14 gene (279) is required for lethal infection of mice (277). Recently, it was shown that mig14 encodes an inner membrane-associated protein that promotes persistent infection, survival within macrophages, and resistance to an antimicrobial peptide (23).…”
Section: Fun Genesmentioning
confidence: 84%
“…Antigen localization within the Salmonella cell might also affect immune recognition, with accessible surface antigens being potentially more protective. However, the putative function of Mig-14 as a transcription factor (42) suggests that at least this partially protective antigen resides in the Salmonella cytoplasm. Surface localization can be directly determined by using proteome techniques (43), but this is difficult for ex vivo samples.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the regulation and function of the Salmonella gene mig-14, which is dependent on PhoP for transcriptional activation within cultured macrophages (53) and contributes to oral virulence in mice (51). We demonstrate here that the mig-14 promoter is activated in minimal medium containing limiting concentrations of magnesium, low pH, or antimicrobial cationic peptides.…”
mentioning
confidence: 99%
“…In addition to restoring PB resistance with pmrD, we could also partially restore PB resistance to the mig-14 strain with a mig-14-expressing plasmid (data not shown). This plasmid had been previously used to complement the mig-14 mutant for virulence in oral infection of mice (51). mig-14 is not required for addition of 4-aminoarabinose to LPS.…”
mentioning
confidence: 99%